PHILOSOPHICAL FOUNDATIONS OF AN INCLUSIVE SOCIETY: THE CASE OF UZBEKISTAN (Educa Journal of Studies, 2026)
This article examines human dignity as a fundamental philosophical principle underlying the formation of an inclusive social order. Drawing on the ideas of Kant, Rawls, and the capability approach of Amartya Sen and Martha Nussbaum, the study analyzes dignity as an intrinsic value that ensures equality, justice, and social participation. The paper argues that respect for human dignity serves as a normative foundation for inclusive policies and institutions, enabling the integration of diverse social groups. Particular attention is given to the relationship between dignity and social inclusion in the context of contemporary societal transformations. The study concludes that the realization of human dignity is a necessary condition for building a sustainable and cohesive society.
Keywords: Social cohesion, equality, inclusive society, equality, human rights, values, capabilities, diversity.